The Effectiveness of Pregnancy Gymnastics in Reducing Low Back Pain in Pregnant Women in the Third Trimester at the Tamalate Health Center, Makassar - Sitti Nur Ain; Hidayati hidayati; Agustina Ningsi; Ros Rahmawati; Andi Syintha Ida (Afiyatun Journal of Health Sciences, 2026)
ABSTRACT Background: Low back pain is a common musculoskeletal complaint in late pregnancy and may interfere with mobility, sleep quality, daily activities, and maternal comfort. Pregnancy exercise is a feasible non-pharmacological intervention that can be integrated into antenatal services, particularly in primary health care. However, local evidence from community health centers remains limited. Objective: This study aimed to compare the level of low back pain before and after pregnancy exercise among third-trimester pregnant women at Tamalate Public Health Center, Makassar. Methods: This pre-experimental study used a one-group pretest-posttest design. Thirty-six third-trimester pregnant women with low back pain were selected using purposive sampling. Pain intensity was assessed before and after the intervention using a structured pain questionnaire/numeric pain scale. Data were analyzed descriptively and using the Wilcoxon signed-rank test because the paired data were ordinal or not normally distributed. Results: Before the intervention, 17 respondents (47.2%) reported severe pain, 14 (38.9%) moderate pain, and 5 (13.9%) mild pain. After the intervention, severe pain decreased to 1 respondent (2.8%), while mild pain increased to 20 respondents (55.6%). The Wilcoxon test showed a significant reduction in pain after pregnancy exercise (Z = -5.215; p < 0.001), with a large effect size (r = 0.87). Conclusion: Pregnancy exercise was associated with a significant reduction in low back pain among third-trimester pregnant women. Nevertheless, the absence of a control group, the relatively small sample size, and the subjective nature of pain measurement should be considered when interpreting the findings. Keywords: low back pain; pregnancy exercise; third trimester; pregnant women; pretest-posttest ABSTRAK Latar Belakang: Nyeri punggung bawah merupakan keluhan muskuloskeletal yang sering dialami ibu hamil trimester III dan dapat mengganggu mobilitas, kualitas tidur, aktivitas sehari-hari, serta kenyamanan ibu selama kehamilan. Senam hamil merupakan intervensi nonfarmakologis yang relatif mudah diterapkan dalam pelayanan antenatal, khususnya pada layanan primer. Akan tetapi, bukti lokal mengenai penerapannya di tingkat puskesmas masih perlu diperkuat. Tujuan: Penelitian ini bertujuan membandingkan tingkat nyeri punggung bawah sebelum dan sesudah senam hamil pada ibu hamil trimester III di Puskesmas Tamalate, Makassar. Metode: Penelitian ini menggunakan desain pre-eksperimental dengan pendekatan one-group pretest-posttest. Sampel terdiri atas 36 ibu hamil trimester III dengan nyeri punggung bawah yang dipilih menggunakan purposive sampling. Tingkat nyeri diukur sebelum dan sesudah intervensi menggunakan kuesioner/skala nyeri terstruktur. Data dianalisis secara deskriptif dan menggunakan uji Wilcoxon signed-rank karena data berpasangan bersifat ordinal atau tidak berdistribusi normal. Hasil: Sebelum intervensi, 17 responden (47,2%) mengalami nyeri berat, 14 responden (38,9%) nyeri sedang, dan 5 responden (13,9%) nyeri ringan. Setelah intervensi, nyeri berat menurun menjadi 1 responden (2,8%), sedangkan nyeri ringan meningkat menjadi 20 responden (55,6%). Uji Wilcoxon menunjukkan penurunan nyeri yang bermakna setelah senam hamil (Z = -5,215; p < 0,001), dengan ukuran efek besar (r = 0,87). Kesimpulan: Senam hamil berhubungan dengan penurunan nyeri punggung bawah pada ibu hamil trimester III. Namun, hasil perlu diinterpretasikan dengan mempertimbangkan tidak adanya kelompok kontrol, ukuran sampel yang relatif kecil, dan sifat subjektif pengukuran nyeri.